Multi-agent path finding (part B) - Cao, Lifeng (Nanyang Technological University, 2020)
Multi-Agent Pathfinding (MAPF) is the problem of finding paths efficient collision-free paths for sets of agents with a designated start and end goal. This project aims to implement and evaluate the algorithms suitable for the MAPF problem in real-time with the involvement of a waypoint. In the project, the agents will be passing through waypoints before they reach from start node to goal node. Therefore, common MAPF algorithms such as A* algorithm and Conflict Based Search(CBS) will be used to evaluate using varies cost functions. Experimental results will also be compared between various existing algorithms to access the performance of these algorithms.